Metode Seni Drama Dalam Pembelajaran Simulasi Pelayanan Rumah Sakit Dalam Lab. Administrasi Rumah Sakit STIKES DONA Palembang - Nita Novianti (Universitas PGRI Palembang, 2023)
The notion of drama is something that is known so far, which for example states that drama is a story or an imitation of human behavior that is staged which is not wrong. This is because when viewed from the words of the drama itself, the definition of drama above is considered appropriate. In dramaturgy, form is taken into account as an overall concept of how to experience a role so that we can give the concept according to what we want in the event. It should be remembered, in dramatugi it is necessary to study human behavior in context to achieve its goals and not to study the results of its behavior in these events. In dramaturgy, it is necessary to understand that in interactions between humans is behavior that is approved and can lead to the ultimate goal of the purpose of social interaction in the event. In general, this research uses a descriptive method, namely a method that is as relative as possible to explain and describe, analyze, and interpret as well. Qualitative research is data collected by researchers in the form of words, sentences or pictures that have a more meaningful meaning so that they are able to trigger a real understanding of any description of something that is not just a presentation of numbers and also frequency. In addition to primary data, there are also observations in drama learning in the fourth semester of the Medical Record and Health Information Study Program at Stikes Dona Palembang. Secondary data is in the form of writings related to drama learning with the art method of playing drama based on project learning obtained from various sources in the form of simulations carried out in the administrative laboratory of the RMIK Stikes Dona Palembang hospital. In drama learning it is also necessary to appreciate drama not only focusing on cognitive aspects which involve affective and psychomotor aspects by carrying out activities such as during administrative services to develop the imagination and readiness of the students themselves in activities in designing hospital administration. Keywords: method, drama, service